Embolic Diseases - Evolving Diagnostic and Management Approaches 2020
DOI: 10.5772/intechopen.85005
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia and Pregnancy: Diagnosis and Management

Abstract: Thromboembolic disease during pregnancy is a significant cause of maternal morbidity and mortality involving venous or arterial thrombosis and possible clinical manifestations like clinical symptoms of antiphospholipid antibody syndrome and hyperhomocysteinemia. For diminishing the prevalence of thromboembolic disease, the early identification of pregnant women with various risk factors for thrombosis without clinical symptoms is of great importance. However, the optimal management for asymptomatic pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 64 publications
(252 reference statements)
1
16
0
Order By: Relevance
“…However, during pregnancy, normal changes occur in the coagulation system of a woman. A reduction in free and total S protein and also a raise in coagulation factors Vc, VIIIc, Xc, and von Willebrand factor antigen are observed [ 6 ]. As we saw in our 30-week gestation case, fetal death appears to have resulted from massive placental thrombosis, while the mechanisms associated with preeclampsia are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during pregnancy, normal changes occur in the coagulation system of a woman. A reduction in free and total S protein and also a raise in coagulation factors Vc, VIIIc, Xc, and von Willebrand factor antigen are observed [ 6 ]. As we saw in our 30-week gestation case, fetal death appears to have resulted from massive placental thrombosis, while the mechanisms associated with preeclampsia are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of APS in pregnancy ranges from 0 to 11% (with an average of 2%). However, the APS is detected in up to 37% of cases with SEL [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean Section (CS) rates have been increasing in recent decades worldwide, and this is a global problem because of the negative effect on maternal and neonatal health [ 1 ]. Although CS is a very common surgery, it is associated with an increased risk of hemorrhage, uterine bladder and bowel injury, postoperative sepsis, postoperative ileus [ 2 ] and thromboembolic events [ 3,4 ]. Some studies on neonatal complications have shown that CS is associated with an increased risk for the infant's obesity, diabetes, respiratory morbidity, and atopic dermatitis in childhood [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital thrombophilia is more often associated with some hereditary abnormalities. [1,2] In general population, incidence of congenital thrombophilia depends on the type of disorder. The appearance of antithrombin, C-protein and protein S (natural coagulation inhibitors) deficiency is about 1% in the general population.…”
Section: Introductionmentioning
confidence: 99%